Combination of anti-CGRP/CGRP-R mAbs with onabotulinumtoxin A as a novel therapeutic approach for refractory chronic migraine: a retrospective study of real-world clinical evidence and a protocol for a double-blind, randomized clinical trial to establish the efficacy and safety - Corasaniti, M. T.; Lawrence, G. W.; Bagetta, G.; Iannacchero, R.; Tarsitano, A.; Monteleone, A.; Pagliaro, M.; Tonin, P.; Sandrini, G.; Nicotera, P.; Scuteri, D. (Frontiers in Pharmacology, 2023)
Chronic migraine is a disabling neurovascular disorder that ranks amongst the top causes of years lived with disability worldwide. The duration and the frequency of migraine affects cognitive and affective domains, inducing worsening of memory and executive functions and of orientation and causing anxiety. Population-based studies report a worrying level of resistance to treatments. Therefore, this study aims: 1) to assess efficacy of monoclonal antibodies (mAbs) directed towards the calcitonin gene-related peptide (CGRP) or its receptor (CGRP-R) for chronic migraine resistant to current preventatives; 2) to design a clinical trial protocol to evaluate efficacy and safety of combination therapy utilizing anti-CGRP/CGRP-R together with onabotulinumtoxin A in patients suffering from resistant chronic migraine; 3 to provide molecular rationale for combination therapy. A controlled trial is warranted as pooled analysis of real-world data from our group highlighted that combined treatment provides ≥50% reduction vs baseline (onabotulinumtoxin A) of monthly headache days (MHDs) in up to 58.8% of patients, but there was only sparse application of this combined therapy to date. The mAbs chosen are: erenumab, because its combination effect with onabotulinumtoxin A improved symptoms in 65% of patients; eptinezumab, due to its faster action. The results highlight that early diagnosis of migraine improves therapeutic outcomes with mAbs alone, confirming their effectiveness and the need for adequately powered clinical trial evaluating the safety and potential superior effectiveness eptinezumab/erenumab and onabotulinumtoxin A together.